Sexual States - Puri, Jyoti (Duke University Press, 2016)
In Sexual States Jyoti Puri uses the example of the efforts to decriminalize homosexuality in India to show how the regulation of sexuality is fundamentally tied to the creation and enduring existence of the state. Between 2001 and 2013 activists attempted to rewrite section 377 of the Indian Penal Code, which outlaws homosexual behavior. Having interviewed activists and NGO workers throughout five metropolitan centers, investigated crime statistics at the National Crime Records Bureau, visited various state institutions, and met with the police, Puri found that section 377 is but one element of the large and complex systems of laws, practices, policies, and discourses that regulate Indian sexuality. Intended to mitigate sexuality's threat to the social order, this regulation works to preserve the views of the state as inevitable, legitimate, and indispensable. By highlighting the various means through which the regulation of sexuality constitutes India's heterogeneous and fragmented